2017
DOI: 10.1371/journal.pone.0169302
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injury Leads to Increased Long-Term Susceptibility to Respiratory Infection in both Mouse Models and Population Studies

Abstract: BackgroundBurn injury initiates an acute inflammatory response that subsequently drives wound repair. However, acute disruption to the immune response is also common, leading to susceptibility to sepsis and increased morbidity and mortality. Despite increased understanding of the impact of burn injury on the immune system in the acute phase, little is known about long-term consequences of burn injury on immune function. This study was established to determine whether burn injury has long-term clinical impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Thus, our data indicates that burn victims could demonstrate reduced T cell functionality for well over 1 year following the injury. This is in line with population studies, which found that burn patients exhibited a heightened risk for respiratory infections in the first five years following burn injury (58). Given that the leading cause of burnrelated mortality are infections, this highlights the urgent need for clinical interventions (1).…”
Section: Discussionsupporting
confidence: 76%
“…Thus, our data indicates that burn victims could demonstrate reduced T cell functionality for well over 1 year following the injury. This is in line with population studies, which found that burn patients exhibited a heightened risk for respiratory infections in the first five years following burn injury (58). Given that the leading cause of burnrelated mortality are infections, this highlights the urgent need for clinical interventions (1).…”
Section: Discussionsupporting
confidence: 76%
“…Burns patients have a lifelong increase in the likelihood of developing a range of chronic inflammatory conditions (9)(10)(11)(12)(13)(14)35). The possibility of immune disruption in acute burn injuries, and more specifically severe burn trauma, has been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory pre-clinical studies in mice, modeling 8% TBSA involvement as a non-severe burn injury (NSBI), have demonstrated changes in innate and adaptive immunity up to 84 days post-injury (14,20). In pediatric patients with severe burn injury, sustained elevation of circulating cytokines has been observed up to 3 years after the injury (21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cytokines and neuropeptides, such as oxytocin, are related to pain and psychological distress [ 53 , 54 ], and significant evidence suggests oxytocin has a neuromodulation role in (traumatic) stress and anxiety [ 53 , 55 ]. Evidence demonstrates that such systemic responses may occur after both severe and minor burns [ 56 59 ]. Given that the majority of paediatric burn admissions are for minor burns, these findings have important health implications.…”
Section: Discussionmentioning
confidence: 99%